DAMPAK PENERAPAN LITERASI DAN INKLUSI KEUANGAN TERHADAP KINERJA UMKM: Studi Kasus Pada UMKM Unit Citra Niaga Samarinda - Rudy Syafariansyah Dachlan; Eko Hendriyadi (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
The objective of this study is to examine the impact of financial literacy and inclusion on the performance of Micro, Small, and Medium Enterprises (MSMEs) at the Citra Niaga Samarinda Unit. The research adopts a descriptive quantitative approach. Financial inclusion and financial literacy are considered as independent variables, whereas the performance of UMKM Citra Niaga Samarinda Unit is the dependent variable. A total of 67 respondents were included as samples in this study. Data collection involved interviews, questionnaires, and documentation. To test the hypothesis, the analysis employed multiple linear regression, conducting both partial and simultaneous tests. The findings of the analysis suggest that financial literacy and financial inclusion collectively influence the performance of MSMEs. However, when examined individually, only financial inclusion demonstrates a significant effect.